Hydrothermal synthesis of rGO-PbBi2Se4 composite and investigation of its structural, chemical and field emission properties - Aher, Rahul; Bhorde, Ajinkya; Sharma, Priyanka; Nair, Shruthi; Borate, Haribhau; Pandharkar, Subhash; Rondiya, Sachin; Chaudhary, Minakshi; Gopinath, Chinnakonda; Suryawanshi, Sachin; More, Mahendra; Jadkar, Sandesh (Journal of Materials Science-Materials in Electronics, 2018)
In the present study we report the one step facile synthesis of pristine lead bismuth selenide (PbBi2Se4) and reduced graphene oxide (rGO) and its composites with PbBi2Se4. Formation of pristine PbBi2Se4 and rGO-PbBi2Se4 composite were confirmed by X-ray diffraction and X-ray photoelectron spectroscopy. The surface morphology and topography investigated by using scanning electron microscopy and transmission electron microscopy revealed the formation of nano-flowers pristine PbBi2Se4. After coupling pristine PbBi2Se4 with rGO the surface morphology shows the formation of sharp vertically protruded nano-sheets/nano-flaks originated from the nano-flowers. Finally, the field emission properties of pristine PbBi2Se4 and rGO-PbBi2Se4 composite have been investigated. It has been observed that the rGO-PbBi2Se4 composite emitter exhibited excellent field emission properties with low turn-on field (similar to 2.8 V/A mu m for 10 A mu A/cm(2)), high emission current density (similar to 1288 A mu A/cm(2) at 3.9 V/A mu m) and superior current stability (similar to 4.5 h for similar to 1 A mu A) compare to pristine PbBi2Se4 emitter. Thus, the facile one step synthesis approach and robust nature of rGO-PbBi2Se4 composite emitter can provide prospects for the future development of large-area emitter applications such as flat-panel-display and vacuum micro/nanoelectronics devices.